THE EFFECT OF FINANCIAL PERFORMANCE AND GOOD CORPORATE GOVERNANCE ON SUSTAINABILITY REPORT DISCLOSURE - Faradilla, Annisa Rafika; Subadriyah, Subadriyah (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
Many social and environmental problems are caused by the operational activities of companies, especially those in the mining sector. Therefore, companies must be responsible for the environment in which they operate and then disclose this in their sustainability reports. This study aims to determine the effect of profitability, leverage, company size, board of commissioners, and institutional ownership on sustainability report disclosure. This research is a quantitative research. The population of this study is mining sector companies listed on the Indonesia Stock Exchange for the period 2020-2022, with a total population of 63 companies. The sampling technique for this study used a purposive sampling method and obtained 18 companies multiplied by the research period of 3 years, resulting in a total sample of 54 sample data. This study uses secondary data obtained from the annual reports and sustainability reports of mining sector companies listed on the Indonesia Stock Exchange for the period 2020-2022. The analytical model used in this study is multiple linear regression analysis. The results of this study indicate that company size has a significant positive effect on sustainability report disclosure. Meanwhile, profitability, leverage, board of commissioners, and institutional ownership do not have a significant effect on sustainability report disclosure.